2019
DOI: 10.3390/antibiotics8010009
|View full text |Cite
|
Sign up to set email alerts
|

New Chloramphenicol Derivatives from the Viewpoint of Anticancer and Antimicrobial Activity

Abstract: Over the last years, we have been focused on chloramphenicol conjugates that combine in their structure chloramphenicol base with natural polyamines, spermine, spermidine and putrescine, and their modifications. Conjugate 3, with spermidine (SPD) as a natural polyamine linked to chloramphenicol base, showed the best antibacterial and anticancer properties. Using 3 as a prototype, we here explored the influence of the antibacterial and anticancer activity of additional benzyl groups on N1 amino moiety together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…If we compare the TPP analogs of CHL with the nearest structural analogs exhibiting antimicrobial activity, in which two pharmacophores are conjugated through the alkyl linker, we can note that the antibacterial effect of these compounds is due to the fact that they either bind to bacterial ribosomes or inhibit translation in bacteria, like polyamide analogs of CHL [ 49 , 50 ], or disrupt the membrane potential of bacteria, since the alkyl TPP conjugates with fluorescein [ 22 , 23 ] or coumarin [ 20 , 21 ], while CAM-Cn-TPPs can exhibit both these effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we compare the TPP analogs of CHL with the nearest structural analogs exhibiting antimicrobial activity, in which two pharmacophores are conjugated through the alkyl linker, we can note that the antibacterial effect of these compounds is due to the fact that they either bind to bacterial ribosomes or inhibit translation in bacteria, like polyamide analogs of CHL [ 49 , 50 ], or disrupt the membrane potential of bacteria, since the alkyl TPP conjugates with fluorescein [ 22 , 23 ] or coumarin [ 20 , 21 ], while CAM-Cn-TPPs can exhibit both these effects.…”
Section: Resultsmentioning
confidence: 99%
“…CHL has been frequently used as a platform to obtain derivatives with an increased potency [ 46 ]. This drug is especially amenable to chemical derivatization, because its dichloroacetyl moiety can be easily replaced with a variety of other chemical scaffolds, such as amino acids [ 47 ], peptides [ 48 ], and an acyl group carrying the polyamine extension [ 49 , 50 ], endowing it with new properties. Thus, the synthesis of novel CHL analogs containing a TPP cation in their structure represents a promising challenge in terms of creating new potential dual-acting antibiotics and antiproliferative agents.…”
Section: Introductionmentioning
confidence: 99%
“…This drug is especially amenable to chemical derivatization because its dichloracetyl moiety can be easily replaced with a variety of other chemical scaffolds, such as amino acids [ 13 ], peptides [ 14 ], or other acyl-carrying groups [ 15 ], rendering it with new properties. For example, in one of the previous studies, CHL analogs with the dichloroacetyl moiety replaced by a polyamine extension that carries a positive charge and hydrophobic phenyl groups showed improved antibacterial and antitumor activities compared to CHL [ 15 , 16 ]. Moreover, recently, we have synthesized several amino acid analogs of CHL and demonstrated that the histidyl-derivative of CHL, which carries aromatic and positively charged side chain, exhibits substantially higher affinity for the bacterial ribosome due to strong stacking interactions of the histidyl moiety of this compound with the nucleotide U2506 of the 23S rRNA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lomefloxacin arrested cell cycle likely due to topoisomerase II inhibition and also caused DNA breakdown at high doses in cultured melanoma human cells [54]. Chloramphenicol and its derivatives inhibited mitochondrial protein synthesis, killing the cancer stem cells [55,56]. Vancomycin has been shown to increase the activity of radiation therapy [57].…”
Section: Discussionmentioning
confidence: 99%